2000
DOI: 10.1007/0-306-47959-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Climate and Vegetation as Driving Factors in Global Fire Activity

Abstract: Abstract:Global active fire distributions have been determined for a 12 month period from daily acquired, low spatial resolution satellite imagery. These distributions have been grouped into a small number of classcs based on thc spatial and temporal characteristics of the data. Agiobai climatology of monthly temperature and precipitation data was used to derive warmth and moisture indices. We show how different patterns of fire activity, as represented by the fire classes, can be related to particular climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
(13 reference statements)
3
20
0
Order By: Relevance
“…By capturing the length of alternate periods of moist and dry conditions, the variables MI and MSL allow us to resolve relationships between climate and fire frequency. We find agreement with pyrogeographic studies on the role of seasonality (Dwyer et al 2000, van der Werf et al 2008, Krawchuk et al 2009, Bowman et al 2014). Limitations in fire activity change as a function of seasonality: growing season length limits biomass (fire fuel) in cold regions, moist season length limits biomass in regions with intermediate growing seasons but it limits vegetation flammability in moist regions with long growing seasons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…By capturing the length of alternate periods of moist and dry conditions, the variables MI and MSL allow us to resolve relationships between climate and fire frequency. We find agreement with pyrogeographic studies on the role of seasonality (Dwyer et al 2000, van der Werf et al 2008, Krawchuk et al 2009, Bowman et al 2014). Limitations in fire activity change as a function of seasonality: growing season length limits biomass (fire fuel) in cold regions, moist season length limits biomass in regions with intermediate growing seasons but it limits vegetation flammability in moist regions with long growing seasons.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships between tree cover, moisture and fire found in our study are similar to the ones found in previous studies (Dwyer et al 2000, Sankaran et al 2005, Bucini and Hanan 2007, van der Werf et al 2008, Hirota et al 2011, Staver et al 2011Fig. 6).…”
Section: Long Growing Seasons (Gsl = 12)supporting
confidence: 91%
See 1 more Smart Citation
“…Relating those to changes in climate is often not straightforward. Fire activity is affected by changes in climate by directly altering lightning ignition sources (Price and Rind, 1994) and fuel moisture (Dwyer et al, 2000;Westerling et al, 2003) and indirectly through changes in fuel availability and vegetation distribution (Westerling et al, 2003;Martin Calvo et al, 2014). The importance of these controlling factors for fire activity varies across climate regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in forest types among distinct vegetation formations are also likely to stem from differences in climatic conditions or fire activities (Koutsias & Karteris 2003, Gedalof et al 2005. Since fire activity, at large scale, depends on resource gradients of e.g., primary productivity (Krawchuk & Moritz 2011), different climatic and vegetation zones are expected to reveal differences in fire activity (Dwyer et al 2000). Similarly, different potential natural vegetation units at national scale may reflect different fire-related characteristics (Vázquez et al 2002).…”
Section: Introductionmentioning
confidence: 99%